INTERAKSI ISLAM DENGAN DENGAN KESENIAN DAN KEBUDAYAAN JAWA - Safa, Safa Salsabila Alfiah Putri (Jurnal Budaya, 2026)
This article examines the interaction between Islam and Javanese culture as a significant phenomenon in the history of Indonesian civilization. Islamization in Java did not occur in a confrontational manner, but rather through a peaceful and adaptive process of acculturation with local culture. This research employed a literature review with a qualitative approach, analyzing various written sources and field interviews. The results indicate that the spread of Islam in Java occurred through trade, marriage, education, and the cultural preaching of the Wali Songo (Nahdlatul Ulama). Arts and culture—such as wayang (wayang), gamelan (gamelan), macapat (traditional Javanese music), and the tradition of selamatan (celebrating ceremonies)—were the primary means of disseminating Islamic values without erasing old traditions. This interaction not only produced religious art forms but also gave birth to a new social and philosophical value system that emphasized balance, tolerance, and harmony between humans, nature, and God. Thus, the integration of Islam and Javanese culture created a distinctive model of Islam in the archipelago that was moderate, polite, and deeply rooted in local wisdom.